Penggunaan Modalitas te mo ii dan te mo kamawanai dalam Percakapan Bahasa Jepang - Damayanti, Mutia; Salsabil, Nabiella; Azzahrani, Rakhma Nur; Rossale, Titus (Ayumi : Jurnal Budaya, Bahasa, dan Sastra, 2021)
This article analyzes the using of te mo ii and te mo kamawanai modalities in Japanese conversation. This article aims to describe the using of the kinshi-kyoka modalities, namely te mo ii and te mo kamawanai along with a comparison of the functions of the two modalities. The researcher obtained data in the form of dialogue discourse on Japanese dramas, and a YouTube channel with the theme of Japanese language education. In analyzing, the researcher used descriptive method to describe the function of the kinshi-kyoka modality marked with te mo ii and te mo kamawanai. Furthermore, to find out the differences and similarities in the modalities of te mo ii and te mo kamawanai, the researchers used a substitution technique. Based on the results of data analysis, it can be concluded that the modalities te mo ii and te mo kamawanai have differences that lie in their equivalent meaning, but have the same use, namely to ask for or give permission. In its use, the modalities of te mo ii and te mo kamawanai can be substituted for each other in the context of giving permission.